Gravitational light-bending prevents [gamma][gamma] absorption in gravitational lenses - Bottcher, Markus; Thiersen, Hannes (Astronomy and astrophysics (Berlin), 2016)
The magnification effect that is due to gravitational lensing enhances the chances of detecting moderate-redshift (z~ 1) sources in very high-energy (VHE; E> 100 GeV) [gamma]-rays by ground-based atmospheric Cherenkov telescope facilities. It has been shown in previous work that this prospect is not hampered by potential [gamma]-[gamma] absorption effects by the intervening (lensing) galaxy, nor by any individual star within the intervening galaxy. In this paper, we expand this study to simulate the light-bending effect of a realistic ensemble of stars. We first demonstrate that for realistic parameters of the galaxy's star field, it is extremely unlikely (probability [<, ~]10 super(-6)) that the direct line of sight between the [gamma]-ray source and the observer passes by any star in the field close enough to be subject to significant [gamma][gamma] absorption. Our simulations then focus on the rare cases where [gamma][gamma] absorption by (at least) one individual star might be non-negligible. We show that gravitational light-bending will have the effect of avoiding the [gamma]-[gamma] absorption spheres around massive stars in the intervening galaxy. This confirms previous results and re-inforces arguments in favour of VHE [gamma]-ray observations of lensed moderate-redshift blazars to extend the redshift range of objects detected in VHE [gamma]-rays, and to probe the location of the [gamma]-ray emission region in these blazars.